A comprehensive review on the sustainable refrigeration systems. (2021) - Gupta, Anupriya; Sankhla, Vijayendra Singh; Sharma, Deepak
Abstract: The objectives for having a refrigerator are to keep the food products cool as it slow down the activity of bacteria. A refrigerator could be mechanically driven or by thermal energy. The technologies which are thermally activated to provide cooling are promising alternatives which not only serve the need for air-conditioning, for augmenting prime movers, dehumidification and refrigeration, but they also conserve energy and safeguards our environment. Waste heat Recovery system, solar refrigeration systems are popularizing because of their ecofriendly nature. Vapor adsorption system, vapor absorption system are critically reviewed in this article. The dependency of human beings on the limited fossil fuels will reduce if the practice of using clean solar energy and complete utilization of waste heat is done. These technologies are gaining huge attention due to their sustainable nature. A vapor absorption refrigeration system has many added advantages when it is compared with the present vapor compression refrigeration system which are emission of no greenhouse gases thereby zero chances of global warming. The COP of the system is less but is more economical and could be readily used for domestic as well as industrial purposes.